Social Changes in Parenting Patterns for Young Parents Using Mobile Touch Screen Devices (MTSD) in Makassar City - Mega Mustikasari, Muhammad Syukur, Najamuddin, Syamsu A Kamaruddin (South Eastern European Journal of Public Health, 2025)
Introduction: The impact of social change in parenting practices among young parents who use Smartphone Touch Screen Devices (MTSD) in Makassar City. This study was driven by the phenomenon of increasing use of MTSD in the daily lives of young parents, which has an impact on their interactions and parenting patterns. Aims: The main focus of this study is to understand how the impact of MTSD use affects the quality of direct interactions between parents and children, the development of children's social skills, and their physical activities and creative play. Methods: The method used in this study is qualitative with a phenomenological approach. Data were collected through in-depth interviews with young parents in Makassar City who were selected purposively to ensure suitability with the topic being studied. The collected data were analyzed thematically to reveal the impact of parenting practices influenced by MTSD use. Results: The results of this study revealed a significant reduction in direct interactions between parents and children and the environment, which reduced emotional warmth in the relationship between young parents. In addition, there was a decline in children's social skills, as seen from their difficulties in communicating and socializing outside the family environment. Then another thing is that the use of MTSD has an impact on reducing children's physical activity and creative play, because they are more often involved in passive activities such as watching videos or playing games on the device.